Role of Nanotechnology in Futuristic Warfare - Dixit, Ambesh; Kumar, Narendra (Nanotechnology for Defence Applications, 2019)
Although warfare technology is very advanced in terms of the development and availability of deadly directed energy weapons, their delivery platforms, surveillance technologies in acquition of military targets with great accuracy. Three technologies, namely nano, information, and biotechnology, are believed to be the technologies of the twenty-first century that will have their impact felt in the futuristic war scenarios. The combination of information and nanotechnology in the form of artificial intelligence may lead to the replacement of human beings with unmanned intelligent robotic systems performing duties in highly hazardous environments in areas affected by the use of weapons of mass destruction. The nanotechnology-enabled quantum communication may lead to highly secured unbreakable information sharing between friendly forces. Furthermore, a combination of nano- and biotechnologies is expected to generate a new class of nano- and bioweapons hitting human targets even indoors without their presence being noticed by the enemy. Some of such weapons may prove to be the weapons of mass extinction. Nanotechnology on the other hand may also provide protective measures against such weaponries.